Landscape vocabulary in the discursive space of modern Kazakh prose: The lingual-stylistic aspect (based on the material «Anthology of modern Kazakh prose») - Hirutski, А.А.; Аmalbekova, М.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The characterized significance of the anthology output for the Ka-zakh and world culture is characterized. The lexical composition is revealed of landscape vocabulary is revealed, its quantitative characterizing is carried out. It is concluded that the aggregate empirical material sufficiently fully reflects the landscape features of Kazakhstan. A frequency response is given to all identified landscape tokens, which indicates that in the discursive space of anthology for both authors and characters of their works, the deep foundations of life are close-ly connected with the land of the fathers, the land of their ancestors. According to the features of the designated locus, lexical-semantic groups of landscape vocabu-lary are established that detail of the landscape space of the anthology. The artis-tic and stylistic functions are defined and characterized, which performed by landscape vocabulary are defined and characterized. It is concluded that these functions help to reveal new facets of the unique nature of Kazakhstan, as well as the artistic richness of the works presented in the anthology. Key landscape lex-emes are highlighted acting as national-cultural symbols are highlighted.